Polar Topside Ionosphere During Geomagnetic Storms: Comparison of ISIS‐II With TDIM. Issue 7 (14th July 2018) - Sojka, J. J.; Rice, D.; Eccles, V.; David, M.; Schunk, R. W.; Benson, R. F.; James, H. G.
Abstract: Space weather deposits energy into the high polar latitudes, primarily via Joule heating that is associated with the Poynting flux electromagnetic energy flow between the magnetosphere and ionosphere. One way to observe this energy flow is to look at the ionospheric electron density profile (EDP), especially that of the topside. The altitude location of the ionospheric peak provides additional information on the net field‐aligned vertical transport at high latitudes. To date, there have been few studies in which physics‐based ionospheric model storm simulations have been compared with topside EDPs. A rich database of high‐latitude topside ionograms obtained from polar orbiting satellites of the International Satellites for Ionospheric Studies (ISIS) program exists but has not been utilized in comparisons with physics‐based models. Of specific importance is that the Alouette/ISIS topside EDPs spanned the timeframe from 1962 to 1983, a period that experienced very large geomagnetic storms. We use a physics‐based ionospheric model, the Utah State University Time Dependent Ionospheric Model (TDIM), to simulate ionospheric EDPs for quiet and storm high‐latitude passes of ISIS‐II for two geomagnetic storms. This initial study finds that under quiet conditions there is good agreement between model and observations. During disturbed conditions, however, a large difference is seen between model and observations. The model limitation is probably associated with the inability of its topside boundary to replicate strong outflow conditions. As a result, modeling of the ionospheric outflows needs to be extended well into the magnetosphere, thereby moving the upper boundary much higher and requiring the use of polar wind models. Key Points: The paper focuses on prestorm and main phase topside ionospheric response to a mild and a severe geomagnetic storm Simulations from an extensively used F region model, TDIM, are compared to ISIS‐II topside ionosphere observations Surprisingly, the TDIM is unable to simulate the observed storm response while satisfactorily simulating the prestorm topside